Analisis Penerapan Konsep Asuransi Syariah pada Produk Amanah Card di Amanah Takaful Banten - Davis Gufron; Mumu Zainal Mutaqin; Siti Yumsinah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study discusses the implementation of the concept of Islamic insurance in the Amanah Card product at Amanah Takaful Banten. In Indonesia, there are various economic activities such as trade, savings and loans, and Islamic financial institutions. Currently, the insurance sector is growing rapidly in Indonesia. There are two types of insurance in Indonesia, namely Islamic insurance and conventional insurance. However, conventional insurance poses concerns for Muslims due to the presence of elements such as riba (interest), gharar (uncertainty), and maysir (gambling). Therefore, Islamic insurance emerges as a risk protection system that prioritizes Sharia principles. The objectives of this study are: (1) to identify the concept of the Amanah Card product at Amanah Takaful Banten, (2) to examine the implementation of Islamic insurance principles in the Amanah Card product, and (3) to analyze how Amanah Takaful Banten improves the accessibility of the Amanah Card product. This research employs a qualitative approach using a field study method (direct observation in the field). Data were collected through interviews with informants, as well as observation and documentation methods. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. Relevant literature includes theories on insurance, Amanah Card, and zakat management institutions, as well as previous studies that examine the implementation of Islamic insurance concepts in insurance products such as Amanah Card. The results show that the Amanah Card product is categorized as a microinsurance product. It implements Islamic insurance principles, including the use of contracts (akad) and management practices that comply with Sharia principles and do not violate existing regulations. The Amanah Card product can be accessed offline through registration with Duta MT Bertaawun and online through social media and the Amanah Takaful website. In conclusion, the Amanah Card product is considered compliant both from a Sharia perspective and regulatory standards.